O29 Effects of neuromuscular exercises targeting evertors and hip abductors on muscle volume (a mri analysis), strength, and postural control: a six-week randomised controlled trial. (17th September 2017) - Son, SJ; Kim, H; Seeley, MK; Hopkins, JT
Abstract : Study Design: Randomised controlled trial. Objectives: To examine effects of neuromuscular exercises targeting evertors and hip abductors on muscle volume, strength, and postural control. Background: Deficits in postural control and evertor and hip abductor strength are associated with chronic ankle instability (CAI). Neuromuscular exercises seem to improve sensorimotor function, but it is unclear whether improved function is due to muscle size and strength gains or neuromuscular efficiency. Methods and Measures: Fifty-one CAI patients were randomly allocated to control (n=14, 3 dropouts), strength (n=14, 3 dropouts), or strength +balance (n=15, 2 dropouts) group. Forty-three CAI patients (M=29, F=14; 22±2 years, 176±9 cm, 75±11 kg, 4.8±2.5 sprains, 82%±8% FAAM-ADL, 57%±12% FAAM-Sport, 2.7±1.5 MAII) completed the study. Both strength and strength +balance groups completed 5 or 10 neuromuscular exercises targeting evertors and hip abductors, 3 times/week for 6 weeks under supervision. Total volume of evertors and hip abductors was calculated via multi-slice 3D images acquired using a Siemens Trio MRI scanner (TE: 7.48 ms, TR: 17 ms, thickness: 5 mm) and segmented using Analyse 12.0 software. Three trials of maximum voluntary contraction (MVC) was measured using an isokinetic dynamometer (100 Hz). Two trials of single-leg balance was measured using a force plate (50 Hz). A mixed model ANCOVA analysis with repeated measures was used to detect differences for muscle volume (cm 3 /m*kg), MVC (Nm/kg), and postural control (COP-AP and -ML velocity; m/s) over time. Results: ANCOVA analyses revealed no time x group interaction in total volume of evertors (p=0.33), hip abductors (p=0.51), evertor strength (p=0.78), hip abductor strength (p=0.55), and COP-AP velocity (p=0.07), with the only exception in COP-ML velocity (p=0.0002) between the strength +balance and control group (p=0.02). Conclusion: Six weeks of neuromuscular exercises failed to improve muscle volume and strength gains, but static postural control was improved. Six weeks may not be adequate to increase muscle volume and strength.